Letter to Jane Tolmach from Assemblyman Herschel Rosenthal - Herschel Rosenthal:::::: (1976)
This June 9, 1976 mailgram from Assemblyman Herschel Rosenthal congratulates Jane Tolmach on her primary victory. He expressed enthusiasm about working with her to advance shared Democratic ideals and humorously noted that a desk was being polished and a nameplate ordered for "Assemblywoman Jane Tolmach."